Art and Design Education of Students of Galicia in the Late 19th and Early 20th Centuries - Volynska, Olena (Pedagogical Discourse, 2025)
An important issue today is the development of such an education system that will not only contribute to the acquisition of knowledge, skills and abilities of schoolchildren, but will also become the basis for the restoration and development of the economy of the post-war state of Ukraine. A significant role in the outlined problem is played by the study of the progressive experience of the past, namely: art and design education of schoolchildren of Galicia in the late 19th - early 20th centuries. Our study analyzed the cultural prerequisites for the development of art and design education of schoolchildren of Galicia in the late 19th - early 20th centuries. The artistic and pedagogical processes that took place at the beginning of the 20th century are characterized in general and in particular, their influence on the development of art and design education of schoolchildren of Galicia is traced. The pedagogical achievements of Galician artists are studied. The teaching methods and forms of conducting classes in art disciplines of D. Golembyovsky, M. Kots, V. Krytsinsky, etc. are highlighted. It is noted that an artist-teacher is a highly qualified mentor who, using the right methods, develops the artistic worldview of students, educates competent artists, teachers and hardworking citizens who understand and create true art, visit museums, art galleries, shape reality according to the laws of beauty, etc. The importance of such artistic disciplines as drawings, folk art, history of Ukrainian and foreign art, handicrafts, etc. in the art and design education of the region’s youth is analyzed. It is determined that a mandatory condition for art and design education of youth is the publication and provision of educational institutions with textbooks and manuals on art disciplines. Attention is drawn to the special importance of national culture and the influence of folk art on the art education of the region’s student youth and the importance of using the results of the research in modern Ukraine.